3D CFD simulation of a circulating fluidized bed with on-line adjustment of mechanical valve. (1st December 2015) - Liu, Cenfan; Zhao, Mingzhao; Wang, Wei; Li, Jinghai
Abstract: Past computational fluid dynamics (CFD) simulations on circulating fluidized bed (CFB) are all based on static geometries. To better understand the real operating performance of CFBs and make the simulation closer to virtual experiment, this work is to introduce on-line adjustment of solids flow rate via a mechanical valve in simulation. The two-fluid model (TFM) is used as the governing equations, for which the solids stress is closed by using the kinetic theory of granular flow and the drag is closed by using the EMMS/matrix scheme. The sliding mesh model is used to mimic the dynamic change of the opening or closing of the valve. And its effects on the flow behavior are studied by investigating the variation of axial voidage profile and solids flux in the riser under different solids inventories. The simulation results are in qualitative agreement with experimental observation, as detailed in the literature (Li et al., 1998. Chem. Eng. Sci. 53, 3367–3379). This work can be expected to be a starting point for the virtual process engineering, the next paradigm of CFD simulation. Highlights: A CFB with on-line adjustment of valve is simulated with CFD. The dynamic response of flow of CFB agrees with the experiment. This is a first step toward the virtual process engineering, an emerging CFD paradigm.